THE IMPLEMENTATION OF THE PANCASILA STUDENT PROFILE STRENGTHENING PROJECT (P5) IN INSTILLING THE VALUE OF MUTUAL COOPERATION AMONG STUDENTS AT SMP NEGERI 21 SAMARINDA.: PENERAPAN PROYEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) DALAM MENANAMKAN NILAI GOTONG ROYONG PADA PESERTA DIDIK DI SMP NEGERI 21 SAMARINDA - m ikhsan maula ikhsan; Asnar Asnar; Alim Salamh; Jawatir Pardosi (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This study aims to examine the implementation of the Pancasila Student Profile Strengthening Project (P5) in instilling the value of mutual cooperation among students at SMP Negeri 21 Samarinda and to identify supporting and inhibiting factors. This research employed a descriptive qualitative approach with observation, interviews, and documentation as data collection techniques. The results indicate that P5 implementation promotes collaboration, shared responsibility, and social awareness among students. The study concludes that P5 is effective in instilling mutual cooperation values when implemented systematically and collaboratively.